2012
DOI: 10.1160/th11-11-0768
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation use by patients with atrial fibrillation in Germany

Abstract: Atrial fibrillation (AF) is the most common significant cardiac rhythm disorder. Oral anticoagulation (OAC) is recommended by guidelines in the presence of a moderate to high risk of stroke. Based on an analysis of claims-based data, the aim of this contribution is to quantify the stroke-risk dependent OAC utilisation profile of German AF patients as well as the possible causes and the associated clinical outcomes of OAC under-use. Our data set was derived from two large mandatory German medical insurance fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(34 citation statements)
references
References 46 publications
5
29
0
Order By: Relevance
“…The emergence of sex as an important factor in OAC use is consistent with multiple previous studies demonstrating that OAC tends to be underutilized in women with AF. 8,14 Our study extends prior observations by indicating that women also are started on OAC later than their male counterparts, with 73% of men being on OAC at 1 month versus only 70% of women. Although the reason for this disparity is not entirely clear, this gender gap may be an important target for improving care quality since women with AF are at greater stroke risk compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The emergence of sex as an important factor in OAC use is consistent with multiple previous studies demonstrating that OAC tends to be underutilized in women with AF. 8,14 Our study extends prior observations by indicating that women also are started on OAC later than their male counterparts, with 73% of men being on OAC at 1 month versus only 70% of women. Although the reason for this disparity is not entirely clear, this gender gap may be an important target for improving care quality since women with AF are at greater stroke risk compared to their male counterparts.…”
Section: Discussionsupporting
confidence: 87%
“…Comorbidities prevalent at AF diagnosis were defined using the presence of at least 1 ICD-9 code for a given condition at any time prior to the index AF encounter in a manner similar to that used in previous studies. 8,11 Baseline medication use was defined as the presence of a medication prescription within 30 days prior to AF diagnosis. Reversible AF was defined as the concomitant presence of AF with an ICD-9 code diagnosis corresponding to cardiac surgery or thyroid disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As one respondent noted, 'Some patients that should have been treated with oral anticoagulants were not treated in the past because of the challenges of VKA therapy, but now they can be treated with NOACs.' Under-usage of oral anticoagulants in the pre-and early-NOAC era was also reported in other developed countries and availability of NOACs reduced the undertreated population (14,15). Similar observations were also recorded in our study, as data analysis revealed that the treated population increased from an average of 7.4 % per year to almost 55.000 in 2015 (Table I).…”
Section: Populationsupporting
confidence: 90%
“…However, numerous studies have shown that ‘high-risk' patients are often undertreated [7,8]. We are also getting better at handling warfarin with efforts to improve the quality of international normalized ratio control, as reflected by the average time within therapeutic range [9], as well as the availability of novel OAC that overcome the many limitations of warfarin [10,11].…”
mentioning
confidence: 99%